A potassium niobate@zinc indium sulfur composite material and its preparation method and application
Through the potassium niobate @ zinc indium sulfur composite material, the unique structure of potassium niobate and the layered structure of zinc indium sulfur are used to solve the problem of photogenerated carrier composite in zinc indium sulfur materials, and the photocatalytic hydrogen production performance is improved, so as to achieve It has an efficient and stable photocatalytic effect and has a green and environmentally friendly preparation method.
Patent Information
- Application Number
- CN202310984267.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The rapid recombination of photogenerated carriers in zinc-indium sulfur materials limits the photocatalytic hydrogen production performance, and the prior art is difficult to effectively improve the efficiency of photohydrogen production.
Potassium niobate @ zinc indium sulfur composite material, by combining potassium niobate with zinc indium sulfur, the unique crystal structure and energy band structure of potassium niobate promote photogenerated carrier separation, combining suitable calcination temperature and solution components Regulate to form a stable composite material.
The photogenerated carrier separation efficiency of the photocatalyst is improved, the photocatalytic activity and stability are maintained for a long time, the operation is simple and the cost is low, and toxic raw materials and expensive equipment are not used.
Smart Images

Figure CN117019174B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalytic composite materials, and in particular relates to a potassium niobate@zinc indium sulfur composite material and a preparation method and application thereof. Background Art
[0002] Solar hydrogen production technology is an important way to alleviate the energy and environmental crisis. Research in this field originated in 1972, when Fujishima, Honda and others used TiO2 thin films to produce hydrogen by photoelectrochemical reaction to decompose water. Since then, scientists have developed many semiconductor photocatalysts, including metal oxides, sulfides, and nitrides. Among them, sulfide semiconductors have the advantage that the conduction band potential is generally higher than the reduction potential of water, so they are considered to be good materials for photocatalytic water decomposition and hydrogen production. On this basis, scholars have found that zinc indium sulfur, as a representative of ternary sulfides, has an atomic layered structure and a suitable band structure, and is more suitable as a photocatalytic water decomposition and hydrogen production material than binary sulfides. Because the layered structure of the photocatalytic water decomposition and hydrogen production material can not only shorten the diffusion distance of the photogenerated carriers, but also provide more active sites for the photochemical reaction. More importantly, their band structure can be regulated until it is most suitable for photocatalytic water decomposition and hydrogen production. However, the photogenerated carriers are easy to recombine quickly in the zinc indium sulfur material, which seriously limits the performance of photocatalytic hydrogen production. Summary of the invention
[0003] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a potassium niobate@zinc indium sulfur composite material.
[0004] Another object of the present invention is to provide a method for preparing the potassium niobate@zinc indium sulfur composite material.
[0005] Another object of the present invention is to provide an application of the potassium niobate@zinc indium sulfur composite material.
[0006] The present invention is achieved by providing a method for preparing a potassium niobate@zinc indium sulfur composite material, the method comprising the following steps:
[0007] (1) potassium carbonate, niobium oxide and ammonium chloride are uniformly mixed and placed in a muffle furnace, heated at a heating rate of 2 to 3°C / min, calcined at 500 to 900°C for 3 to 6 hours, and then cooled to room temperature and collected to obtain potassium niobate;
[0008] (2) dispersing the potassium niobate in a mixed solution of diethylenetriamine and ethylene glycol, adding indium salt, zinc salt and sulfur source, and stirring to obtain a reaction precursor solution;
[0009] (3) transferring the reaction precursor solution to a polytetrafluoroethylene reactor, reacting at a solvent thermal temperature of 150 to 200° C. for 10 to 36 hours, cooling the reaction product to room temperature, washing, and drying to obtain a potassium niobate@zinc indium sulfur composite material, wherein the mass proportion of potassium niobate in the composite material is 1 to 90%.
[0010] Preferably, in step (1), the mass ratio of potassium carbonate, niobium oxide and ammonium chloride is 0.1-0.9:0.2-1:0.1-10.
[0011] Preferably, in step (2), the molar ratio of zinc, indium and sulfur in the indium salt, zinc salt and sulfur source is x:x:x+1.
[0012] Preferably, in step (2), the indium salt is selected from at least one of indium acetate, indium nitrate, indium chloride and indium sulfate; the zinc salt is selected from at least one of zinc acetate, zinc nitrate, zinc chloride and zinc sulfate; and the sulfur source is selected from at least one of thiourea, sulfur powder, sodium sulfide and thioacetamide.
[0013] Preferably, in step (2), the volume ratio of diethylenetriamine to ethylene glycol in the mixed solution is 20-40 mL:20-40 mL.
[0014] Preferably, in step (3), the washing is washing with distilled water and ethanol in sequence, repeated three times; and the drying is drying at 60°C.
[0015] The invention further discloses a potassium niobate@zinc indium sulfur composite material prepared by the method.
[0016] The present invention further discloses the application of the potassium niobate@zinc indium sulfur composite material in the preparation of a catalyst for photocatalytic water splitting to produce hydrogen.
[0017] The present invention overcomes the deficiencies of the prior art and provides a potassium niobate@zinc indium sulfur composite material and its preparation method and application. In the present invention, by compounding zinc indium sulfur with other materials, the separation of photogenerated carriers can be promoted, thereby improving the photocatalytic hydrogen production performance. Considering the band matching principle required for the composite formation of photocatalysts by different semiconductor materials, as well as the stability and cost issues required by the photocatalytic system, the present invention selects potassium niobate material for the composite of zinc indium sulfur. Potassium niobate has a unique crystal structure and band structure, composed of corner-sharing octahedral NbO6, and has a one-dimensional microchannel, which is conducive to promoting carrier transport. In the preparation method of the present invention, the structure of potassium niobate is affected by the mass of ammonium chloride and the calcination temperature. The ratio of potassium niobate and zinc indium sulfur can be regulated through the experimental process. The ion adsorption on the surface of potassium niobate and the slow release process of sulfur ions are the key to the in-situ formation of the composite material.
[0018] Compared with the shortcomings and deficiencies of the prior art, the present invention has the following beneficial effects:
[0019] (1) The preparation of the composite material of the present invention does not use any toxic raw materials and expensive equipment, nor does it use harsh reaction conditions. The preparation method has the characteristics of simple operation, low cost, and green environmental protection;
[0020] (2) The composite material of the present invention can effectively improve the separation efficiency of photogenerated carriers in the catalyst; since the composite material of potassium niobate and zinc indium sulfur is synthesized in situ, there is a close contact interface between potassium niobate and zinc indium sulfur, and the physical and chemical properties are stable, which can maintain the photocatalytic activity and stability of the composite material for a long time;
[0021] (3) The present invention provides a new perspective for the development of efficient potassium niobate@zinc indium sulfur composite materials and has universal applicability in the field of composite nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is an X-ray diffraction diagram of the composite material 1 in the embodiment of the present invention;
[0023] Figure 2 is a scanning electron microscope photograph of the composite material 1 in the embodiment of the present invention;
[0024] Figure 3 is the light absorption performance of the composite material 1 in the effect embodiment of the present invention;
[0025] Figure 4 is the energy band structure of the composite material 1 in the embodiment of the present invention;
[0026] Figure 5 is a photoelectron spectrum of the composite material 1 in the embodiment of the present invention; wherein a is a zinc spectrum, b is an indium spectrum, c is a sulfur spectrum, d is a potassium spectrum, e is a niobium spectrum, and f is an oxygen spectrum;
[0027] Figure 6 This is a comparison chart of the photocatalytic hydrogen production performance data of the composite material 1 and other materials in the effect embodiment of the present invention;
[0028] Figure 7 It is a data chart of hydrogen production stability of composite material 1 in the effect embodiment of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] Example 1
[0031] (1) 3 g of potassium carbonate, 5.8 g of niobium oxide, and 6 g of ammonium chloride were uniformly mixed and calcined in a muffle furnace at 850° C. for 5 hours at a heating rate of 2° C. / min. After the mixture was calcined, the mixture was cooled to room temperature and potassium niobate was collected;
[0032] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 30 ml of diethylenetriamine and 30 ml of ethylene glycol, adding 2 mol of indium chloride tetrahydrate, 2 mol of zinc acetate dihydrate, and 5 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0033] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 180° C. for 24 hours, and after cooling to room temperature, centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times; the obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 1; wherein the mass proportion of potassium niobate in the composite material 1 was 10%.
[0034] Example 2
[0035] (1) 3 g of potassium carbonate, 5.8 g of niobium oxide, and 8 g of ammonium chloride were uniformly mixed and calcined in a muffle furnace at 800° C. for 5 hours at a heating rate of 2° C. / min. After the mixture was calcined, the mixture was cooled to room temperature and potassium niobate was collected;
[0036] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 20 ml of diethylenetriamine and 40 ml of ethylene glycol, adding 1.8 mol of indium chloride tetrahydrate, 1.8 mol of zinc acetate dihydrate, and 4.6 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0037] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 180° C. for 24 hours. After cooling to room temperature, the solution was centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times. The obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 2 (the mass percentage of potassium niobate in the composite material was 25%).
[0038] Example 3
[0039] (1) 3 g of potassium carbonate, 5.8 g of niobium oxide, and 10 g of ammonium chloride were uniformly mixed and calcined in a muffle furnace at 800° C. for 5 hours at a heating rate of 2° C. / min. After the mixture was calcined, the mixture was cooled to room temperature and potassium niobate was collected;
[0040] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 30 ml of diethylenetriamine and 30 ml of ethylene glycol, adding 1.6 mol of indium chloride tetrahydrate, 1.6 mol of zinc acetate dihydrate, and 4.5 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0041] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 160° C. for 12 hours. After cooling to room temperature, the solution was centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times. The obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 3 (the mass proportion of potassium niobate in the composite material was 40%).
[0042] Example 4
[0043] (1) 4 g potassium carbonate, 6.8 g niobium oxide, and 8 g ammonium chloride were uniformly mixed and calcined in a muffle furnace at 750° C. for 5 hours at a heating rate of 2° C. / min. After the mixture was calcined, the mixture was cooled to room temperature and potassium niobate was collected;
[0044] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 40 ml of diethylenetriamine and 20 ml of ethylene glycol, adding 1 mol of indium chloride tetrahydrate, 1 mol of zinc acetate dihydrate, and 3 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0045] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 160° C. for 36 hours. After cooling to room temperature, the solution was centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times. The obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 4 (the mass percentage of potassium niobate in the composite material was 55%).
[0046] Example 5
[0047] (1) 1.5 g potassium carbonate, 2.5 g niobium oxide, and 5 g ammonium chloride were uniformly mixed and calcined in a muffle furnace at 500° C. for 6 hours at a heating rate of 3° C. / min. After the mixture was calcined, the mixture was cooled to room temperature and potassium niobate was collected;
[0048] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 40 ml of diethylenetriamine and 20 ml of ethylene glycol, adding 2 mol of indium chloride tetrahydrate, 2 mol of zinc acetate dihydrate, and 5 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0049] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 150° C. for 10 hours, and after cooling to room temperature, centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times; the obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 5 (the mass proportion of potassium niobate in the composite material was 1%).
[0050] Example 6
[0051] (1) 12 g of potassium carbonate, 23 g of niobium oxide, and 24 g of ammonium chloride were uniformly mixed and calcined in a muffle furnace at 500° C. for 6 hours at a heating rate of 3° C. / min. After the mixture was calcined, it was cooled to room temperature and potassium niobate was collected;
[0052] (2) dispersing the potassium niobate prepared in step (1) in a mixed solution of 40 ml of diethylenetriamine and 20 ml of ethylene glycol, adding 1 mol of indium chloride tetrahydrate, 1 mol of zinc acetate dihydrate, and 3 mol of thioacetamide, and stirring the mixture to form a reaction precursor solution;
[0053] (3) The pre-reaction solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200° C. for 36 hours. After cooling to room temperature, the solution was centrifuged and washed with distilled water and ethanol in sequence, and the process was repeated three times. The obtained solid was dried at 60° C. for 10 hours to obtain a potassium niobate@zinc indium sulfur composite material 6 (the mass percentage of potassium niobate in the composite material was 90%).
[0054] Effect Example
[0055] The embodiment of the present invention uses the composite material 1 prepared in the above embodiment 1 as an object for physical, chemical and catalytic performance analysis.
[0056] 1. Structural component analysis
[0057] The above composite material 1 was analyzed and the results were as follows: Figures 1 to 7 shown.
[0058] from Figure 1 It can be seen that the characteristic peaks of potassium niobate and zinc indium sulfur exist, thus proving that the material is a composite material of potassium niobate and zinc indium sulfur.
[0059] from Figure 2 It can be seen that small pieces of ZnInS grow on the surface of rod-shaped KNbO3.
[0060] from Figure 3 It can be seen that the composite material has good ultraviolet light absorption performance and can also absorb part of visible light. The maximum absorption band edge is approximately 450nm.
[0061] from Figure 4 It can be seen that potassium niobate and zinc indium sulfide have staggered band structures, their valence bands are 2.71eV and 1.36eV, and their conduction band positions are -0.51eV and -1.06eV, respectively.
[0062] Figure 5 is the photoelectron spectrum of composite material 1, where Figure 5 a is the zinc spectrum, Figure 5 b is the indium spectrum, Figure 5 c is the sulfur spectrum, Figure 5 d is the potassium spectrum, Figure 5 e is the niobium spectrum, Figure 5 f is the oxygen spectrum. Among them, Figure 5 a-c show that the peaks of Zn 2p, In 3d, and S2p move toward the direction of increasing binding energy, while Figure 5 The peaks of K2p, Nb 2p, and O1s in d to f move toward the direction of decreasing binding energy. This phenomenon indicates that the electron density of ZnInS decreases, while the electron density of KNbO3 increases. Therefore, for the KNbO3@ZnInS composite material, the electrons at the interface are transferred from ZnInS to KNbO3.
[0063] 2. Catalytic performance analysis
[0064] An online photocatalytic device (Beijing Bofeilai Online Photocatalytic Analysis System Labsolar-6A) was used to conduct a water decomposition hydrogen production experiment. A 300W xenon lamp (equipped with a 400nm filter) was used as a visible light source. 20 mg of the synthesized potassium niobate @ zinc indium sulfur composite material 1 was dispersed in 80 ml of an aqueous solution (containing 0.3M sodium sulfide / 0.25M sodium sulfite), and 1% of Pt nanoparticles were in situ photodeposited as a co-catalyst. Complete degassing was performed before visible light irradiation to remove the air dissolved in the aqueous solution. An ethanol circulating cold trap was used throughout the process to control the photocatalytic reaction temperature at 6°C. The generated gas products were quantitatively analyzed online using a gas chromatograph (FULI 979011) and a TCD detector.
[0065] The results are as follows Figures 6-7 As shown, Figure 6 This is a comparison chart of the photocatalytic hydrogen production activity data of various materials, which shows that the photocatalytic water splitting hydrogen production activity of potassium niobate@zinc indium sulfur composite material is significantly better than the photocatalytic hydrogen production of potassium niobate and zinc indium sulfur materials alone, and the hydrogen production activity is affected by the proportion of potassium niobate in the composite material. The final ranking is potassium niobate@zinc indium sulfur-10>potassium niobate@zinc indium sulfur-25>potassium niobate@zinc indium sulfur-40>potassium niobate@zinc indium sulfur-55>zinc indium sulfur>potassium niobate. Figure 7 This is a data chart of the hydrogen production stability of composite material 1. After four cycles of photocatalytic hydrogen production tests, it was found that the hydrogen production activity of composite material 1 remained basically unchanged. Therefore, it can be seen from the figure that potassium niobate@zinc indium sulfur composite material 1 has good photocatalytic hydrogen production performance.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a potassium niobate@zinc indium sulfur composite material, characterized in that: The method comprises the following steps: (1) potassium carbonate, niobium oxide and ammonium chloride are uniformly mixed and placed in a muffle furnace, heated at a heating rate of 2 to 3°C / min, calcined at 500 to 900°C for 3 to 6 hours, and then cooled to room temperature and collected to obtain potassium niobate; (2) dispersing the potassium niobate in a mixed solution of diethylenetriamine and ethylene glycol, adding indium salt, zinc salt and sulfur source, and stirring to obtain a reaction precursor solution; (3) The reaction precursor solution is transferred to a polytetrafluoroethylene reactor, reacted at a solvent thermal temperature of 150 to 200° C. for 10 to 36 hours, the reaction product is cooled to room temperature, washed and dried to obtain a potassium niobate@zinc indium sulfur composite material for preparing a photocatalytic water splitting hydrogen production catalyst, wherein the mass proportion of potassium niobate in the composite material is 1 to 90%.
2. The method according to claim 1, characterized in that In step (1), the mass ratio of potassium carbonate, niobium oxide and ammonium chloride is 0.1-0.9:0.2-1:0.1-10.
3. The method according to claim 1, characterized in that In step (2), the indium salt is selected from at least one of indium acetate, indium nitrate, indium chloride and indium sulfate; the zinc salt is selected from at least one of zinc acetate, zinc nitrate, zinc chloride and zinc sulfate; and the sulfur source is selected from at least one of thiourea, sulfur powder, sodium sulfide and thioacetamide.
4. The method according to claim 1, characterized in that In step (2), the volume ratio of diethylenetriamine to ethylene glycol in the mixed solution is 20-40 mL:20-40 mL.
5. The method according to claim 1, characterized in that In step (3), the washing is performed by washing with distilled water and ethanol in sequence, which is repeated three times; and the drying is performed by drying at 60°C.
6. The potassium niobate@zinc indium sulfur composite material prepared by the method according to any one of claims 1 to 5.
